Measurement of total triiodo-L-thyronine in rat serum by homologous radioimmunoanalysis (Revista Española de Fisiología, 1986)
A radioimmunoanalysis comparative study of total tri-iodo-L-thyronine patterns in human and rat sera revealed a quantitative difference between the amounts of labelled antigen which associated with the specific antibody in each case.At the same time, in another experiment, three different protein concentrations were dissolved in rat serum standards producing the results that, at lower protein concentrations a larger quantity of antigen/antibody complex was formed.These changes must be kept in mind for the L-T3 measurement in rat serum.